Taxonomy of the genus Andrikothelyna Pace, 2000 (Coleoptera: Staphylinidae: Aleocharinae), with description of three new species from Taiwan and Japan - Nozaki, Tsubasa (Zootaxa, 2023)
The rove beetle genus Andrikothelyna Pace, 2000 is reviewed. Speiraphallusa Pace, 2013 is synonymized with Andrikothelyna due to the morphological similarities. A revised diagnosis and redescription of the genus are presented, and three new species are described. As a result of this study, this genus consists of the following two known species and three new species: Andrikothelyna papuana Pace, 2000, from Papua New Guinea; Andrikothelyna orientis (Pace, 2013) comb. nov. from Malaysia; Andrikothelyna rubiginosa sp. nov. from Taiwan (Nantou); Andrikothelyna limbata sp. nov. from Japan (Honshu, Kyushu and Ryukyu); and Andrikothelyna naomichii sp. nov. from Japan (Ryukyu). This study reports the newly recorded presence of the genus Andrikothelyna in Taiwan and Japan. In addition, the key to the species is given and the taxonomic position of the genus is discussed. Observation of the living individuals reveals part of the biology of the new species.